Modelagem de uma perna de robô com base no mecanismo de Bennett - Oliveira Júnior, Anezio Alves de (2006)
The purpose of this work is to present the development of a robotic leg, based on a four-bar 4R spatial mechanism, named as Bennett s mechanism. Using an adequate configuration of this mechanism, it is possible to describe a spatial curve, which is similar to the profile of a gait, using only one degree of freedom. Due to its simplicity, the modeled leg is simpler than the legs which are currently used on the mobile robots. To make easy the obstacles transposition, another two degrees of freedom had been added to the leg, allowing it a higher mobility. These aditional degrees of freedom don t compromise the performance of the structure because they are used just during the crossing of the obstacle, where the robot normally moves at lower speeds. The modeled leg, although not to have its configuration optimized, it has presented good results, being capable of crossing obstacles of considerable dimensions, comparing to its own dimensions. Graphical simulations have shown that the physical dimensions of the structure influence the dimensions of the obstacle that the leg can transpose.